ANALYSIS OF THE INFLUENCE OF FINANCIAL REPORT FRAUD, FINANCIAL PERFORMANCE, AND SUSTAINABILITY DISCLOSURE ON COMPANY VALUE - Mohamad Afrizal Miradji; Widiar Onny Kurniawan; Bayu Adi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This research aims to investigate the effects of financial performance, corporate social responsibility (CSR) disclosure, sustainability reporting, corporate governance, and environmental impact on the valuation of firms listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. The employed methodology is a quantitative framework that uses multiple linear regression to analyze secondary data from annual and sustainability reports. The findings demonstrate that financial performance has a positive and significant effect on corporate value. Furthermore, CSR and sustainability disclosures enhance corporate valuation, while effective corporate governance promotes transparency and bolsters investor confidence. These findings suggest that organizations adopting policies focused on financial performance, social responsibility, and sustainability can enhance their market value. This study advances the fields of accounting and management science and provides substantive practical implications for corporate governance